The Dominican friars in Southern Africa : a social history, 1577-1990 - Denis, Philippe, 1952- (Studies in Christian Mission, 1998)
The purpose of this book is to gather in a single narrative the rather disparate stories of Dominican friars in Southern Africa over the past four centuries. Dominicans from Portugal and Portuguese India were present in South-East Africa from 1577 to 1835. Patrick Raymond Griffith, an Irish Dominican, became the first resident bishop in South Africa in 1837. A Dominican mission was established in 1917 with the arrival of a group of English friars. A second group arrived from the Netherlands in 1932. The aim is to provide a social history of the Dominicans in Southern Africa, that is, a history that deals specifically with the social and cultural factors of historical development. The Dominicans ministered in a political, social and cultural context which impacted on their apostolic activities and, in turn, was affected by them. The book's terminus ad quem is 1990, when the National Party opened a process of political negotiation, thus ending more than forty years of apartheid rule.